Exploring Language Learners' Engagement with Influencer Content for English Language Learning on Social Media Platforms - Safitri, Ni Putu Dianita; Tari, Nirmala (Jurnal Simki Pedagogia, 2025)
The growing popularity of social media has made them favored platforms for language learners seeking engaging and authentic language learning content. This study explores how language learners utilize influencer content on social media platforms to learn English. The researchers used questionnaires to find out why learners like this content, what challenges they face, and how it affects their language learning strategies. The study's findings show that language learners actively enjoy using influencer content for learning English on social media. One important finding is that authenticity in language learning content is crucial. Influencers' natural way of communicating immerses learners in the language, boosting their motivation and proficiency. The research used different types of questions and found that learners are highly motivated to access influencer content that is engaging, relatable, and authentic. Learners find influencer language learning to be a refreshing and interactive option compared to traditional classroom methods. The content analysis demonstrates the vital role played by influencers in providing diverse language learning materials. These materials include grammar explanations, vocabulary exercises, and conversational practice, speaking tips, listening comprehension, reading comprehension, and writing skills. Participants appreciate how accessible and flexible influencer content allows them to personalize their learning based on their language skills and interests. In conclusion, this study emphasizes the significant impact of influencers in making language learning on social media platforms more effective. The engaging and authentic content from influencers offers promising opportunities to improve language learners' experiences and skills.